2014
DOI: 10.1016/j.jsha.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Late stent fracture – A potential role of left ventricular dilatation

Abstract: Different anatomical coronary settings have been described as predisposing factors to stent fracture. Consequently, the remodeling of the left ventricle, together with the rise in diastolic pressure, may have affected the shear stress of LAD stents by increasing mechanical forces produced in the diastolic phase on the epicardial vessel. In addition, left ventricular enlargement could have increased the elongation forces on the stent frames by altering the curvature of the stent. All predisposing factors of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Additionally, neoatherosclerosis and uncovered stent struts were reported as the primary cause of late thrombosis in 35% cases and 10% cases, respectively [24]. Although coronary stent fracture is an underrecognized event, it has been reported frequently in the drug-eluting stent era [25]. However, investigators have shown that technical problems with first-generation eluting stent implantations in STEMI patients were associated with higher inhospital mortality and posthospital target vessel failure or cardiac death [24].…”
Section: Contributing Factors Of Adverse Cardiacmentioning
confidence: 99%
“…Additionally, neoatherosclerosis and uncovered stent struts were reported as the primary cause of late thrombosis in 35% cases and 10% cases, respectively [24]. Although coronary stent fracture is an underrecognized event, it has been reported frequently in the drug-eluting stent era [25]. However, investigators have shown that technical problems with first-generation eluting stent implantations in STEMI patients were associated with higher inhospital mortality and posthospital target vessel failure or cardiac death [24].…”
Section: Contributing Factors Of Adverse Cardiacmentioning
confidence: 99%